Exploring the impact of workplace fun and job satisfaction among non-academic staff in UiTM Campus Samarahan and UiTM Campus Samarahan 2: a cross-sectional study / Dayang Nurulnazirah Awang Nong Che and Nurul Aimi Aisyah Mohammad Iskandaria - Awang Nong Che, Dayang Nurulnazirah; Mohammad Iskandaria, Nurul Aimi Aisyah (2024)
A fun workplace is important since it is a fundamental component of employee satisfaction. A sense of happiness helps people to have a positive mind, enjoy high levels of wellbeing and have better mental health. Fun influences job satisfaction, dedication, creativity, energy, organizational citizenship behavior, and productivity, and negatively absenteeism, anxiety, emotional exhaustion, turnover, and burnout (Tews et. al., 2012 as cited in Miiceldili 2016). A pleasant workplace is one where employees are more dependable and effective. Employees get to communicate with one another and create stronger bonds during enjoyable events, which further helps them to work better as a team because social interaction lowers communication barriers. Fun is a type of medicine that, if taken by employees, improves their morale, productivity, excitement, decreases complaints of boredom, and, most importantly, makes them happy both on and offthe job (Soundarapandiyan, K., et al., 2018). For employees, having fun at work is a crucial aspect of job happiness. It promotes improved performance, higher customer satisfaction scores, and employee retention (Attebery, 2017 as cited in M. Zani and Samanol, 2022).This is supported by past research on some characteristics of fun including fun activities and management support for establishing a fun atmosphere and activities for employees, improving working relationships and increasing involvement in the learning process (Tews et al., 2017, 2014). Workplace fun has recently been recognised as an essential component of organizational life, and scholars have taken an interest in studying it and incorporating it into organizational processes. Happiness strongly correlates with pleasant working success and typically increases measures of success as well as better effects that increase workplace results (Boehm and Lyubomirsky, 2008 as cited in M. Rasli et al., 2017). An employee's tenure can be defined as their length ofservice (Ng and Feldman, 2013 as cited Woods et. al., 2017), how long an employee has been with his or her current employer, (Copeland, 2019) and the number of years an employee has been with an organization (Ahmad, et. al., 2021).